Spontaneous Globe Rupture due to Neglected Glaucoma: How can it be? Poster Presentation - Case Report - General practitioner - Firdausi, Asri Ayu; Kunhermawan, Cosmas Hascaryanto; Lestari, Chindhia Rima Rochmatika Bunga (Majalah Oftalmologi Indonesia, 2023)
IntroductionGlobe rupture is usually associated with spontaneous traumatic processes with the worst prognosis.The occurrence without prior trauma is only reported in small numbers of cases. This paper willdescribe a globe rupture in glaucomatous eye and share our experience with its management. Case IllustrationA 66-year-old male presented to the emergency department (ED) with reddish and progressive painin the right eye (RE) followed by severe headaches for the last three days. On history taking, thepatient complained of a progressive blurry vision to total blindness of his RE for 1 year. The patientadmitted to having a history of glaucoma on previous primer examination but did not routinelycontrol it. On initial examination, the patient was hypertensive , and suddenly began bleeding within10 minutes upon arrival at ED. The diagnosis of globe rupture was made and he underwentemergency evisceration. DiscussionSpontaneous globe rupture is very rare, with an incidence of 3 per 100.000 in the United States,while no definite number is found in Indonesia due to the rarity. In glaucoma patients, spontaneousglobe rupture is postulated to occur due to suprachoroidal hemorrhage. Our patients had multiplerisk factors such as advanced age, systemic hypertension, and chronic untreated glaucoma.Evisceration went down to reduce pain, stop bleeding and prevent the spread of infection.Performing surgery within 10 days of the initial injury suggests a lower risk of post-operativeendophthalmitis or sympathetic ophthalmia. ConclusionSpontaneous globe rupture in neglected chronic glaucoma has a very poor outcome but preventable.